1982
DOI: 10.2151/jmsj1965.60.5_1063
|View full text |Cite
|
Sign up to set email alerts
|

Eliassen-Palm Flux Diagnostics and the Effect of the Mean Wind on Planetary Wave Propagation for an Observed Sudden Stratospheric Warming

Abstract: Eliassen-Palm (E-P) flux whose direction is interpreted as that of planetary wave propagation in the meridional plane, is used for diagnosing planetary waves for the 1973 sudden stratospheric warming. E-P flux by zonal wavenumber 1 component was focused into the polar stratosphere prior to the circulation reversal. By the focusing there occurred the intense convergence of E-P flux which embodies the forcing of waves on mean flow. The convergence brought about the intense deceleration of mean zonal wind and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

1984
1984
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…Our results reveal that while the 2009 prewarming period was characterized by vertically propagating waves, the split SSW itself was characterized by the signature of resonance. This result is in qualitative agreement with previous observational studies that showed that split-SSW prewarming periods are characterized by planetary waves with significant westward tilt, while the warmings themselves are characterized by wave events with little to no vertical phase tilt (Kanzawa 1980(Kanzawa , 1982Naujokat et al 2002).…”
Section: Introductionsupporting
confidence: 92%
“…Our results reveal that while the 2009 prewarming period was characterized by vertically propagating waves, the split SSW itself was characterized by the signature of resonance. This result is in qualitative agreement with previous observational studies that showed that split-SSW prewarming periods are characterized by planetary waves with significant westward tilt, while the warmings themselves are characterized by wave events with little to no vertical phase tilt (Kanzawa 1980(Kanzawa , 1982Naujokat et al 2002).…”
Section: Introductionsupporting
confidence: 92%
“…Following Palmer (1981Palmer ( , 1982 and Kanzawa (1982), the TEM formulation are expressed by, where (see Appendix A for undefined terms).…”
Section: Formulationmentioning
confidence: 99%
“…This definition of EP flux is simple even though the dimension is not correctly written. If this EP flux divided by RTs it is EP flux for unit volume (Kanzawa, 1982), and if by ps it is EP flux for unit mass (Palmer, 1982).…”
Section: Formulationmentioning
confidence: 99%
“…On the other hand, Palmer (1981a, b), O'Neill and Youngblut (1982) and Kanzawa (1982) analyzed the satellite data and showed that just before the sudden warming, the distribution of mean zonal winds has larger refractive index in the high latitudinal region than as usual, and that planetary waves which propagate southward in ordinary situation are directed northward. Such an extraordinary configuration of the mean zonal winds could be helpful to the growth of planetary wave.…”
Section: Introductionmentioning
confidence: 99%